Identification of Key Carcinogenic Genes in Colon Adenocarcinoma - Yangbin Dai; Zhenjian Jiang; Yanru Qiu; Yiping Kang; Huangzhen Xu; Tianwen Xu (Tehran University of Medical Sciences, 2022)
Background: We aimed to probe carcinogenic genes associated with colon adenocarcinoma (COAD) development. Methods: The gene expression profile of COAD were downloaded from TCGA. Differentially expressed genes (DEGs) were identified; GO and KEGG pathway enrichment were analyzed. Applying the up-mRNA-and-down-miRNA pairs and the down-mRNA-and-up-miRNA pairs, the miRNA target network was generated. The important genes were further analyzed towards the influence on overall survival and immune infiltration. In addition, essential miRNAs were selected for expression validation using real-time qPCR. Results: Together, from 2020-2021, in Central Laboratory of the Second Affiliated Hospital of Fujian Medical University, we found 3060 up-regulated transcripts and 2254 down-regulated transcripts in mRNA expression, with 235 up-regulated and 263 down-regulated miRNAs. We discovered 98 enriched GO terms using the upregulated DEGs and 315 enriched GO terms using downregulated DEGs. There were 14 enriched KEGG pathways based on the down-regulated DEGs and only one pathway based on the up-regulated DEGs. There were 61 up-mRNA-and-down-miRNA pairs, including 7 miRNAs and 41 carcinogenic targets, among which HOXC13, FOXL2NB, ALOXE3, and ZIC2 were found related to a poorer OS. ZIC2 located at the subnet with the most targets (the miR-129-5p subnet). ZIC2 expression was correlated with immune-cell infiltration. Conclusion: These risk genes, interaction networks, and enrichments may provide a better understanding of the complex molecular mechanisms in COAD development and potential therapeutic targets for clinical treatment of COAD.